2012
DOI: 10.3390/s120303327
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing and Expression of Virulence in Pectobacteria

Abstract: Quorum sensing (QS) is a population density-dependent regulatory mechanism in which gene expression is coupled to the accumulation of a chemical signaling molecule. QS systems are widespread among the plant soft-rotting bacteria. In Pectobacterium carotovorum, at least two QS systems exist being specified by the nature of chemical signals involved. QS in Pectobacterium carotovorum uses N-acylhomoserine lactone (AHL) based, as well as autoinducer-2 (AI-2) dependent signaling systems. This review will address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 109 publications
(183 reference statements)
5
87
0
3
Order By: Relevance
“…According to the working model of QS regulation in Pectobacterium species, high levels of ExpI leads to a reduction of rsmA expression, which ultimately results in higher level of PCWDEs gene expression83940. In agreement with this model, in our experiments we observed that under control conditions, rsmA displayed low expression patterns in both strains.…”
Section: Discussionsupporting
confidence: 88%
“…According to the working model of QS regulation in Pectobacterium species, high levels of ExpI leads to a reduction of rsmA expression, which ultimately results in higher level of PCWDEs gene expression83940. In agreement with this model, in our experiments we observed that under control conditions, rsmA displayed low expression patterns in both strains.…”
Section: Discussionsupporting
confidence: 88%
“…PGPR are able to stimulate plant growth by direct or indirect mechanisms, like production of phytohormones, mineralization of organic matter, and competing with pathogens (Ortiz-Castro et al, 2009). Some Pseudomonas and Vibrio species were considered to be potential pathogen to wetland plants (Pollumaa et al, 2012). Previously, QS has been shown to control Ti plasmid transfer in tumor-forming Agrobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, QS has been shown to control Ti plasmid transfer in tumor-forming Agrobacterium spp. and virulence factor production in soft-rotting P. carotovorum (Pollumaa et al, 2012; Lang et al, 2016). Communication via diffusible signaling molecules between plants and bacteria has been proposed to be one of the important regulators in symbiotic behaviors (Scott et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…have a large impact on the progress of the disease, as their production leads to the degradation of invaded plant tissue (2,3). The production of these enzymes is dependent on cell density and regulated by quorum sensing through N-acetylhomoserine lactone (5) and intracellular regulators (6,7). Motility and nutrient uptake are also factors influencing phytopathogenicity (4,(8)(9)(10).…”
mentioning
confidence: 99%